More than 100 000 farmers increased their productivity based on climate-site-specific agronomy recommendations in LAM - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
About 100 000 farmers in Colombia benefit from climate-site-specific-agronomy-analysis generated by CIAT and Partners . Fedearroz and Fenalce adjusts their blanket recommendation systems with site-specific CSA practices identified by analysis. The former increased 15% its production and reduces 18 % of costs; benefiting 3000 farmers; Fenalce increased 24% its yields and benefit 3335 famers. The- Secretary-of-Agriculture-and-Rural-Development-Pereira used the analysis to identify 119 groups of agroecological-zones within 55923 hectares benefiting 90000 farmers. In Mexico, through MasAgro 4000 farmers access to data-driven-CSA-practices.